Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) \(\frac{3}{5}x-\frac{1}{2}=-\frac{1}{7}\)
\(\Rightarrow\frac{3}{5}x=\left(-\frac{1}{7}\right)+\frac{1}{2}\)
\(\Rightarrow\frac{3}{5}x=\frac{5}{14}\)
\(\Rightarrow x=\frac{5}{14}:\frac{3}{5}\)
\(\Rightarrow x=\frac{25}{42}\)
Vậy \(x=\frac{25}{42}.\)
c) \(5-\left|3x-1\right|=3\)
\(\Rightarrow\left|3x-1\right|=5-3\)
\(\Rightarrow\left|3x-1\right|=2\)
\(\Rightarrow\left[{}\begin{matrix}3x-1=2\\3x-1=-2\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}3x=3\\3x=-1\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=3:3\\x=\left(-1\right):3\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=1\\x=-\frac{1}{3}\end{matrix}\right.\)
Vậy \(x\in\left\{1;-\frac{1}{3}\right\}.\)
d) \(\left(1-2x\right)^2=9\)
\(\Rightarrow\left(1-2x\right)^2=\left(\pm3\right)^2\)
\(\Rightarrow1-2x=\pm3.\)
\(\Rightarrow\left[{}\begin{matrix}1-2x=3\\1-2x=-3\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}2x=-2\\2x=4\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=\left(-2\right):2\\x=4:2\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\)
Vậy \(x\in\left\{-1;2\right\}.\)
Chúc bạn học tốt!
\(2A\left(x\right)-B\left(x\right)=2\left(3x^3+2x^4-x^2+8x-7\right)-\left(-x^4-4x^2-2x^3-7+3x\right)\)
\(=4x^4+6x^3-2x^2+16x-14+x^4+2x^3+4x^2-3x+7\)
\(=5x^4+8x^3+x^2+13x-7\)
a)\(\left(4x+1\right)\left(x-3\right)-\left(x-7\right)\left(4x-1\right)=15\)
\(4x^2-11x-3-\left(4x^2-29x+7\right)=15\)
\(4x^2-11x-3-4x^2+29x-7=15\)
\(18x-10=15\)
\(x=\frac{25}{18}\)
b)\(\left(3x-5\right)\left(x+1\right)-\left(3x-1\right)\left(x+1\right)=x-4\)
\(\left(x+1\right)\left(3x-5-3x+1\right)=x-4\)
\(\left(x+1\right).\left(-4\right)-x+4=0\)
\(-4x-4-x+4=0\)
\(x=0\)
\(B\left(x\right)=x^5+3x^3+x=x\left(x^4+3x^2+1\right)=x\left(x^4+x^2+x^2+1+x^2\right)=x\left[x^2\left(x^2+1\right)+x^2+1+x^2\right]\)
\(=x\left[\left(x^2+1\right)\left(x^2+1\right)+x^2\right]=x\left[\left(x^2+1\right)^2+x^2\right]\)
Vì: \(x^2+1>0,x^2\ge0\)nên \(\left(x^2+1\right)^2+x^2>0\)
Vậy B(x) có nghiệm khi x=0
4(x+3)-2(7-3x)=-3
<=> 4x + 12 - 14 + 6x = -3
<=> 4x + 6x = -3 - 12 + 14
<=> 10x = -1
<=> x = \(-\frac{1}{10}\)
\(4\left(x+3\right)-2\left(7-3x\right)=-3\)
\(4x+12-14+6x=-3\)
\(10x-2=-3\)
\(10x=-3+2\)
\(10x=1\)
\(x=1:10\)
\(x=\frac{1}{10}\)